Resultative Predicates in Japanese - Kaori Takamine (Nordlyd: Tromsø University Working Papers on Language & Linguistics, 2007)
Washio (1997; 1999) observes that resultative predicates are divided into two different groups, strong and weak resultatives, depending on ‘patienthood’ of the object. This typology of resultatives seems to capture a point of crosslinguistic variation in resultatives; Japanese has weak but not strong resultatives, while English has both. Washio also observes that there is another group of examples that bears a superficial resemblance to resultatives but constitutes a different phenomenon, hence spurious resultatives. The difference between weak and strong resultatives is made in terms of the ‘affectedness’ of the verb. Thus the typology of resultatives proposed by Washio is semantically grounded. In this paper, I propose: (i) a fine-grained distinction for Washio’s weak resultatives: (ii) a syntactic analysis of the different resultative types. On the basis of syntactic evidence, I argue that there are two types of weak resultatives, an adjunct of VP and a complement of VP within the vP projection. I also argue that spurious resultatives are structurally higher than weak resultatives in Japanese.